Social representations of breastfeeding and infant formula: An exploratory study with mothers and health professionals to inform policy making. (1st August 2020) - Ares, Gastón; Girona, Alejandra; Rodríguez, Raquel; Vidal, Leticia; Iragola, Valentina; Machín, Leandro; de León, Carolina; Bove, Isabel
Abstract: Although several efforts to promote breastfeeding have been implemented worldwide, the prevalence of exclusive breastfeeding in the first 6 months of life remains low. One of the factors responsible for this trend is the widespread sales and marketing of breast-milk substitutes. In this context, the present work aimed at exploring mothers and health professionals' social representations of breastfeeding and infant formula. The study was conducted in Montevideo (Uruguay), as part of the periodic assessment performed by the Uruguayan government to monitor the marketing of breast-milk substitutes according to the OMS/UNICEF NetCode toolkit. A total of 330 mothers of children under 24 months old and 154 health professionals were recruited at 33 health care facilities. Participants were asked to complete two word association tasks, one with breastfeeding and the other with infant formula. Inductive coding was used to classify the responses into categories and dimensions. The structure of the social representations was explored considering the frequency of mention and the average rank of appearance of the categories. Results showed that mothers' social representations mainly positioned breastfeeding as a feeding practice, whereas infant formulas were mainly perceived as a complement to breast-milk that provides support. In the case of health professionals, the social representations of breastfeeding and infant formulas were in line with scientific evidence and health recommendations. These results suggest that efforts to promote breastfeeding should focus on raising public awareness of the risks associated with breast-milk substitutes and on overcoming the systemic barriers to breastfeeding, particularly among working mothers.